Pengaruh Investasi dan Tenaga Kerja terhadap Pertumbuhan Ekonomi Sumatera Barat - Ryan Cahyadi; Novera Martilova (Universitas 17 Agustus 1945 Semarang, 2024)
The main objective of this research is to identify the influence of capital and activity power on the economic development of West Sumatra. Quantitative research method with data collection through monitoring and library research. Data analysis is attempted by trying classical assumptions such as autocorrelation, normality, multicollinearity, and heteroscedasticity. Next, Multiple Linear Regression Experiment, Limiting Coefficient Experiment (R2), and Assumption Experiment using T (partial) experiment and F (simultaneous) experiment are attempted. Information analysis using SPSS 25 proves that the elasticity of capital (X1) partially has a significant effect on economic growth (Y), with a total t of 2.306 which is greater than the t chart of 1.703 and a probability of 0.000. Likewise, the elasticity of activity power (X2) partially has a significant effect on economic growth with a total t value of 6.689 and a probability of 0.000. The F experiment proves that together, the elasticity of capital (X1) and activity power (X2) have a significant effect on economic growth (Y), with a total f number of 0.000 which is smaller than 0.05. The limiting coefficient (R2) of 0.831 proves that 83.1% of the changes in economic growth can be explained by the elasticity of capital and activity power while the remaining 16.9% are influenced by other aspects.